2021
DOI: 10.1364/ao.432364
|View full text |Cite
|
Sign up to set email alerts
|

LED nonlinearity mitigation in LACO-OFDM optical communications based on adaptive predistortion and postdistortion techniques

Abstract: The preinstalled white light emitting diodes (WLEDs) inside buildings can be exploited as an optical source in visible light communications (VLC) motivated by high optical efficiency and low cost. One of the main challenges for VLC is LED nonlinear distortion, which has a detrimental effect on system performance. Estimation and compensation of the LED nonlinear behavior can be accomplished using predistortion or postdistortion techniques. Three compensation techniques are adopted to mitigate the effect of LED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Because of their high peak power, LED chips are susceptible to overheating. Consequently, the high PAPR of the OFDM signal should be reduced until it is fed into the transmitter LEDs before it is sent [31,32].…”
Section: Severalmentioning
confidence: 99%
“…Because of their high peak power, LED chips are susceptible to overheating. Consequently, the high PAPR of the OFDM signal should be reduced until it is fed into the transmitter LEDs before it is sent [31,32].…”
Section: Severalmentioning
confidence: 99%
“…In addition, it has been shown that the temperature also strongly contributes to the efficiency droop by promoting mechanisms such as carrier leakage, Auger recombination, and carrier delocalization [32]. The static nonlinearity model was adopted to estimate the impact of LED nonlinearity in OFDM [18], [19], optimize bias point [33] and to design nonlinear predistorters [20], [34]. Often the static nonlinearity is described with the Rapps model, originally devised for RF power amplifiers [28].…”
Section: A Led Modelsmentioning
confidence: 99%
“…The nonlinearity of LEDs is often misunderstood and the models found in the literature tend to either oversimplify or overcomplicate the matter. For example, some models assume that the nonlinear distortion is static and the instantaneous relationship between the current input to the LED and the output optical power can be described by a polynomial [17]- [20]. Other authors agree that the memory effects reported in multiple papers cannot be neglected and the LED must be modeled as a dynamic nonlinear system [16], [21]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…After the heating stage, the powder stays in the furnace and is cooled down to room temperature before being was with deionized water to get rid of the residues. After that, it is put into a drying oven and heated at 80 o C for 5h (Xi et al, 2021;Elkarim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%